FreeRTOS on a MicroBlaze Soft-Core Processor with Hardware Accelerators - Tcheussi Ngayap, Vanessa Ingrid

Funnel MPC for nonlinear systems with relative degree one - Berger, Thomas; Dennstädt, Dario; Ilchmann, Achim; Worthmann, Karl (SIAM Journal on Control and Optimization)

Quasi feedback forms for differential-algebraic systems - Berger, Thomas; Ilchmann, A.; Trenn, S. (IMA Journal of Mathematical Control and Information)

Minds in Motion – Some Basic Thoughts on AI and Animation - Eckel, Julia; Ehrlich, Nea (In: animationstudies 2.0)

animationstudiesblog 2.0 | Theme: AI and Animation

Intelligence In Between – Documenting AI in Animation - Eckel, Julia (animationstudies 2.0)

Tab2Onto: Unsupervised Semantification with Knowledge Graph Embeddings - Zahera, Hamada Mohamed Abdelsamee; Heindorf, Stefan; Balke, Stefan; Haupt, Jonas; Voigt, Martin; Walter, Carolin; Witter, Fabian; Ngonga Ngomo, Axel-Cyrille (The Semantic Web: ESWC 2022 Satellite Events)

MultPAX: Keyphrase Extraction Using Language Models and Knowledge Graphs - Zahera, H.M.A; Vollmers, Daniel; Sherif, Mohamed Ahmed; Ngomo, Axel-Cyrille Ngonga (The Semantic Web – ISWC 2022)

ONTOCONNECT: Domain-Agnostic Ontology Alignment using Graph Embedding with Negative Sampling - Chakraborty, Jaydeep; Zahera, H.M.A; Sherif, Mohamed Ahmed; Bansal, Srividya K. (2021 20th IEEE International Conference on Machine Learning and Applications (ICMLA))

Learning Concept Lengths Accelerates Concept Learning in ALC - Kouagou, N’Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngomo, Ngonga Axel-Cyrille (ESWC)
Concept learning approaches based on refinement operators explore partially ordered solution spaces to compute concepts, which are used as binary classification models for individuals. However, the number of concepts explored by these approaches can grow to the millions for complex learning problems. This often leads to impractical runtimes. We propose to alleviate this problem by predicting the length of target concepts before the exploration of the solution space. By these means, we can prune the search space during concept learning. To achieve this goal, we compare four neural architectures and evaluate them on four benchmarks. Our evaluation results suggest that recurrent neural network architectures perform best at concept length prediction with a macro F-measure ranging from 38% to 92%. We then extend the CELOE algorithm, which learns ALC concepts, with our concept length predictor. Our extension yields the algorithm CLIP. In our experiments, CLIP is at least 7.5 times faster than other state-of-the-art concept learning algorithms for ALC---including CELOE---and achieves significant improvements in the F-measure of the concepts learned on 3 out of 4 datasets. For reproducibility, we provide our implementation in the public GitHub repository at https://github.com/dice-group/LearnALCLengths
Keywords: dice knowgraphs raki daikiri kouagou heindorf demir ngonga

Pädagogik und Geschlechterverhältnisse in der Pandemie. Analyse und Kritik fragwürdiger Normalitäten
In der Corona-Pandemie werden viele Themen zum Gegenstand öffentlicher Debatten, welche die Erziehungswissenschaft im Allgemeinen und die erziehungswissenschaftliche Frauen- und Geschlechterforschung im Besonderen seit Langem beschäftigen: Reproduktion sozialer Ungleichheit in Bildungskontexten, ungleiche Verteilung privater Sorge-, Erziehungs- und Betreuungsarbeit, Marginalisierung nicht-heteronormativer Lebensformen u.v.m. Das Ringen um eine Rückkehr zur „Normalität“ ist allgegenwärtig. Der Band zeigt aus geschlechtertheoretischer und erziehungswissenschaftlicher Sicht, dass diese Normalität zu den Bedingungen der Krise selbst gehört und eine Rückkehr zu einer solchen Normalität bestehende Herrschaftsverhältnisse fortsetzt. Obwohl die Öffnungen und Schließungen von Schulen und Kindertagesstätten oder die Belastung von Müttern durch „Homeoffice“ und „Homeschooling“ prominente Themen der politischen Streitigkeiten um die Pandemiebekämpfung und ihre Folgen sind und große mediale Aufmerksamkeit bekommen, sind erziehungswissenschaftliche Perspektiven und insbesondere Positionen der erziehungswissenschaftlichen Frauen- und Geschlechterforschung im Diskurs wenig präsent. Dies möchten die Herausgebenden des Bandes ändern. Ausgehend von Schlagworten wie „Systemrelevanz“ oder „Normalität“ und der Frage nach Retraditionalisierung und Professionalisierung vergeschlechtlichter Bildungs- und Erziehungsarbeit in der Pandemie, werden die genannten Problemstellungen offengelegt und weiterführende Fragestellungen und Perspektiven entwickelt. Vor diesem Hintergrund werden wissenschaftliche und politische Konjunkturen kritisch untersucht und mögliche Gegenentwürfe ausgelotet.

Health relevance of lowering postprandial glycaemia in the paediatric population through diet’: results from a multistakeholder workshop - Vinoy, Sophie; Goletzke, Janina; Rakhshandehroo, Maryam; Schweitzer, Lisa; Flourakis, Matthieu; Körner, Antje; Alexy, Ute; van Schothorst, Evert M.; Ceriello, Antonio; Zakrzewski-Fruer, Julia K.; Buyken, Anette (European Journal of Nutrition)
Abstract To summarize current knowledge and gaps regarding the role of postprandial glycaemic response in the paediatric population, a workshop was organized in June 2021 by the European branch of the International Life Science Institute (ILSI). This virtual event comprised of talks given by experts followed by in-depth discussions in breakout sessions with workshop participants. The main pre-specified topics addressed by the workshop organizing committee to the invited speakers and the workshop participants were: (1) the role of glycaemic responses for paediatric health, based on mechanistic insights from animal and human data, and long-term evidence from observational and intervention studies in paediatric populations, and (2) changes in metabolism and changes in dietary needs from infancy to adolescence. Each talk as well as the discussions were summarised, including the main identified research gaps. The workshop led to the consensus on the crucial role on health of postprandial glycaemic response in paediatric population. However, a lack of scientific data has been identified regarding detailed glucose and insulin profiles in response to foods commonly consumed by paediatric populations, as well as a lack of long-term evidence including the need for suitable predictors during childhood and adolescence to anticipate health effects during adulthood.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

The Effect of Regular Consumption of Reformulated Breads on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Schadow, Alena M.; Revheim, Ingrid; Spielau, Ulrike; Dierkes, Jutta; Schwingshackl, Lukas; Frank, Jan; Hodgson, Jonathan M.; Moreira-Rosário, André; Seal, Chris J.; Buyken, Anette; Rosendahl-Riise, Hanne (Advances in Nutrition)
Keywords: Nutrition and Dietetics; Medicine (miscellaneous); Food Science

CausalQA: A Benchmark for Causal Question Answering - Bondarenko, Alexander; Wolska, Magdalena; Heindorf, Stefan; Blübaum, Lukas; Ngonga Ngomo, Axel-Cyrille; Stein, Benno; Braslavski, Pavel; Hagen, Matthias; Potthast, Martin (Proceedings of the 29th International Conference on Computational Linguistics)
At least 5% of questions submitted to search engines ask about cause-effect relationships in some way. To support the development of tailored approaches that can answer such questions, we construct Webis-CausalQA-22, a benchmark corpus of 1.1 million causal questions with answers. We distinguish different types of causal questions using a novel typology derived from a data-driven, manual analysis of questions from ten large question answering (QA) datasets. Using high-precision lexical rules, we extract causal questions of each type from these datasets to create our corpus. As an initial baseline, the state-of-the-art QA model UnifiedQA achieves a ROUGE-L F1 score of 0.48 on our new benchmark.

A parameterized view on the complexity of dependence and independence logic - Kontinen, Juha; Meier, Arne; Mahmood, Yasir (Journal of Logic and Computation)
Abstract In this paper, we investigate the parameterized complexity of model checking for Dependence and Independence logic, which are well studied logics in the area of Team Semantics. We start with a list of nine immediate parameterizations for this problem, namely the number of disjunctions (i.e. splits)/(free) variables/universal quantifiers, formula-size, the tree-width of the Gaifman graph of the input structure, the size of the universe/team and the arity of dependence atoms. We present a comprehensive picture of the parameterized complexity of model checking and obtain a division of the problem into tractable and various intractable degrees. Furthermore, we also consider the complexity of the most important variants (data and expression complexity) of the model checking problem by fixing parts of the input.
Keywords: Logic; Hardware and Architecture; Arts and Humanities (miscellaneous); Software; Theoretical Computer Science

Parameterized Complexity of Logic-Based Argumentation in Schaefer's Framework - Mahmood, Yasir; Meier, Arne; Schmidt, Johannes (Proceedings of the AAAI Conference on Artificial Intelligence)
Logic-based argumentation is a well-established formalism modeling nonmonotonic reasoning. It has been playing a major role in AI for decades, now. Informally, a set of formulas is the support for a given claim if it is consistent, subset-minimal, and implies the claim. In such a case, the pair of the support and the claim together is called an argument. In this paper, we study the propositional variants of the following three computational tasks studied in argumentation: ARG (exists a support for a given claim with respect to a given set of formulas), ARG-Check (is a given set a support for a given claim), and ARG-Rel (similarly as ARG plus requiring an additionally given formula to be contained in the support). ARG-Check is complete for the complexity class DP, and the other two problems are known to be complete for the second level of the polynomial hierarchy and, accordingly, are highly intractable. Analyzing the reason for this intractability, we perform a two-dimensional classification: first, we consider all possible propositional fragments of the problem within Schaefer's framework, and then study different parameterizations for each of the fragment. We identify a list of reasonable structural parameters (size of the claim, support, knowledge-base) that are connected to the aforementioned decision problems. Eventually, we thoroughly draw a fine border of parameterized intractability for each of the problems showing where the problems are fixed-parameter tractable and when this exactly stops. Surprisingly, several cases are of very high intractability (paraNP and beyond).
Keywords: General Medicine

Binary Hermitian Lattices over Number Fields - Kirschmer, Markus; Nebe, Gabriele (Experimental Mathematics)
In a previous paper the authors developed an algorithm to classify certain quaternary quadratic lattices over totally real fields. The present article applies this algorithm to the classification of binary Hermitian lattices over totally imaginary fields. We use it in particular to classify the 48-dimensional extremal even unimodular lattices over the integers that admit a semilarge automorphism.
Keywords: General Mathematics

Driven Gaussian quantum walks - Held, Philip; Engelkemeier, Melanie; De, Syamsundar; Barkhofen, Sonja; Sperling, Jan; Silberhorn, Christine (Physical Review A)
Quantum walks function as essential means to implement quantum simulators, allowing one to study complex and often directly inaccessible quantum processes in controllable systems. In this contribution, the notion of a driven Gaussian quantum walk is introduced. In contrast to typically considered quantum walks in optical settings, we describe the operation of the walk in terms of a nonlinear map rather than a unitary operation, e.g., by replacing a beam-splitter-type coin with a two-mode squeezer, being a process that is controlled and driven by a pump field. This opens previously unattainable possibilities for quantum walks that include nonlinear elements as core components of their operation, vastly extending their range of applications. A full framework for driven Gaussian quantum walks is developed, including methods to dynamically characterize nonlinear, quantum, and quantum-nonlinear effects. Moreover, driven Gaussian quantum walks are compared with their classically interfering and linear counterparts, which are based on classical coherence of light rather than quantum superpositions. In particular, the generation and boost of highly multimode entanglement, squeezing, and other quantum effects are studied over the duration of the nonlinear walk. Importantly, we prove the quantumness of the evolution itself, regardless of the input state. A scheme for an experimental realization is proposed. Furthermore, nonlinear properties of driven Gaussian quantum walks are explored, such as amplification that leads to an ever increasing number of correlated quantum particles, constituting a source of new walkers during the walk. Therefore, a concept for quantum walks is proposed that leads to—and even produces—directly accessible quantum phenomena, and that renders the quantum simulation of nonlinear processes possible.

Domain-aware Text Professionalization using Sequence-to-Sequence Neural Networks - Palushi, Juela

Propaganda Technique Detection Using Connotation Frames - Budanurmath, Vinaykumar

Dealing With Pre-Processing And Feature Extraction Of Time-Series Data In Predictive Maintenance - Manjunatha, Suraj

Analysis of Time-Series Classification in Conditional Monitoring Systems - Kaur , Parvinder

Prescribed signal concentration on the boundary: eventual smoothness in a chemotaxis-Navier–Stokes system with logistic proliferation - Black, Tobias; Wu, Chunyan (Calculus of Variations and Partial Differential Equations)
Keywords: Applied Mathematics; Analysis

Rapid preparation of self-supported nickel–iron oxide as a high-performance glucose sensing platform - Ni, Ming; Tan, Minyuan; Pan, Ying; Zhu, Chuhong; Du, Haiwei (Journal of Materials Chemistry C)
Nickel–iron oxide electrocatalysts prepared via a rapid electrodeposition are promising candidates for non-enzymatic glucose sensors.
Keywords: Materials Chemistry; General Chemistry

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Pay for Tax Certainty? Advance Tax Rulings for Risky Investment under Multi-Dimensional Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren

How Do Tax Technology and Controversy Expertise Affect Tax Disputes? - Dyck, Daniel; Lorenz, Johannes; Sureth-Sloane, Caren

Alte Fotografien, neue Erkenntnisse - Liszt-Rohlf, Verena; Wochnik, Markus; Schwabl, Franziska (Zeitschrift für Berufs- und Wirtschaftspädagogik)
Keywords: Applied Mathematics; General Mathematics

Anne-Christine Brehm, Netzwerk Gotik. Das Ulmer Münster im Zentrum von Architektur- und Bautechniktransfer - Harnack, Maria (Blätter für württembergische Kirchengeschichte)

Im-materiell. Kulturerbe-Studien für Eva-Maria Seng zum 60. Geburtstag

Enhancing attitudes and self-efficacy toward inclusive teaching in physical education pre-service teachers: Results of a quasi-experimental study in physical education teacher education - Grimminger-Seidensticker, Elke; Seyda, Miriam (Frontiers in Education)

Motorische Kompetenzen im Kindesalter: Monitoring, Intervention und Zusammenhänge mit der Selbstwahrnehmung - Strotmeyer, Anne
Motorische Kompetenzen und die Selbstwahrnehmung dieser sind zentral hinsichtlich der Ausbildung eines gesundheitsförderlichen Lebensstils. Bewegungsmangel im Kindesalter und motorische Defizite unterstreichen die Relevanz von Untersuchungen in diesem Forschungsfeld. In diesem Kontext besteht Forschungsbedarf, welcher an der jungen Forschungslinie zu motorischen Basiskompetenzen ansetzt. Daher zielt die vorliegende Arbeit auf die Untersuchung motorischer Basiskompetenzen im Kontext des Monitorings, der Intervention sowie der Untersuchung von Zusammenhängen mit der Selbstwahrnehmung. Es wurden konfirmatorische Faktorenanalysen durchgeführt sowie eine kompetenzorientierte Intervention für das mittlere Kindesalter konzipiert und evaluiert. Zudem fanden Varianzanalysen mit Messwiederholung und manifeste Pfadmodelle Anwendung. Neben der Bestätigung der faktoriellen Struktur des Tests zur Erfassung motorischer Basiskompetenzen (MOBAK 3-4), wurden Zusammenhänge mit endogenen sowie exogenen Faktoren nachgewiesen. Es konnte gezeigt werden, dass mit Hilfe der relativ kurzen Intervention positive Effekte auf die motorischen Basiskompetenzen erzielt werden können. Zudem zeigten sich moderate Korrelationen zwischen motorischen Basiskompetenzen und der Selbstwahrnehmung. Auf Grundlage dieser Befunde sollten im Bereich der Objektkontrolle vor allem motorische Kompetenzen und im Bereich der Lokomotion insbesondere die Selbstwahrnehmung zur Steigerung des Kompetenzlevels gefördert werden.

Lernerkorpora als Ressource in der quantitativen DaF-Forschung - Weber, Tassja (Vermitteln – Verbinden – Verstehen)

Lattice QCD noise reduction for bosonic correlators through blocking - Altenkort, Luis; Eller, Alexander M.; Kaczmarek, O.; Mazur, Lukas; Moore, Guy D.; Shu, Hai-Tao (Physical Review D)

Wundersame Materie. Neomaterialistische Perspektiven auf Relationalität, Wirkmacht und Sprache - Kostan, Anastassija; Hoppe, Katharina (Die Kraft des Staunens: der neue Materialismus in der Gegenwartskunst)

Die Sprache der Materie: Feministische Neomaterialismen zwischen diskursiver Intelligibilität und posthumanistischer Performativität - Kostan, Anastassija (Sociality-Materiality-Practice. Sozialität-Materialität-Praxis)

Woundrous Matter. New Materialist Perspectives on Relationalism, Agency, and Language - Kostan, Anastassija; Hoppe, Katharina (The Power of Wonder. New Materialisms in Contemporary Art)

Feministische Neomaterialismen. Die relationale Immanenz posthumanen Handelns - Kostan, Anastassija

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz-Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

A High-Fidelity Flow Solver for Unstructured Meshes on Field-Programmable Gate Arrays: Design, Evaluation, and Future Challenges - Karp, Martin; Podobas, Artur; Kenter, Tobias; Jansson, Niclas; Plessl, Christian; Schlatter, Philipp; Markidis, Stefano (International Conference on High Performance Computing in Asia-Pacific Region)

Hermeneutik zwischen Logik und Ethik - Ficara, Elena (Ethik in der Hermeneutik – Hermeneutik in der Ethik)

About the structure of the discrete and continuous Eringen’s nonlocal elastica - Cresson, Jacky; Hariz Belgacem, Khaled (Mathematics and Mechanics of Solids)
The Eringen’s nonlocal elastica equation does not possess a Lagrangian formulation. In this article, we find a variational integrating factor which enables us to provide a Lagrangian and Hamiltonian structure associated to this equation. Explicit expressions of the solutions in terms of elliptic integrals of the first kind are then deduced. We then derive discrete version of the Eringen’s nonlocal elastica preserving the Lagrangian and Hamiltonian structure and compare it with Challamel’s and co-worker definition of a discrete Eringen’s nonlocal elastica.
Keywords: Mechanics of Materials; General Materials Science; General Mathematics

CP2K on the road to exascale - Kühne, Thomas; Plessl, Christian; Schade, Robert; Schütt, Ole (arXiv:2205.14741)
The CP2K program package, which can be considered as the swiss army knife of atomistic simulations, is presented with a special emphasis on ab-initio molecular dynamics using the second-generation Car-Parrinello method. After outlining current and near-term development efforts with regards to massively parallel low-scaling post-Hartree-Fock and eigenvalue solvers, novel approaches on how we plan to take full advantage of future low-precision hardware architectures are introduced. Our focus here is on combining our submatrix method with the approximate computing paradigm to address the immanent exascale era.

Parallel quantum chemistry on noisy intermediate-scale quantum computers - Schade, Robert; Bauer, Carsten; Tamoev, Konstantin; Mazur, Lukas; Plessl, Christian; Kühne, Thomas (Phys. Rev. Research)
A parallel hybrid quantum-classical algorithm for the solution of the quantum-chemical ground-state energy problem on gate-based quantum computers is presented. This approach is based on the reduced density-matrix functional theory (RDMFT) formulation of the electronic structure problem. For that purpose, the density-matrix functional of the full system is decomposed into an indirectly coupled sum of density-matrix functionals for all its subsystems using the adaptive cluster approximation to RDMFT. The approximations involved in the decomposition and the adaptive cluster approximation itself can be systematically converged to the exact result. The solutions for the density-matrix functionals of the effective subsystems involves a constrained minimization over many-particle states that are approximated by parametrized trial states on the quantum computer similarly to the variational quantum eigensolver. The independence of the density-matrix functionals of the effective subsystems introduces a new level of parallelization and allows for the computational treatment of much larger molecules on a quantum computer with a given qubit count. In addition, for the proposed algorithm techniques are presented to reduce the qubit count, the number of quantum programs, as well as its depth. The evaluation of a density-matrix functional as the essential part of our approach is demonstrated for Hubbard-like systems on IBM quantum computers based on superconducting transmon qubits.

Roadmap on Electronic Structure Codes in the Exascale Era - Gavini, Vikram; Baroni, Stefano; Blum, Volker; Bowler, David R.; Buccheri, Alexander; Chelikowsky, James R.; Das, Sambit; Dawson, William; Delugas, Pietro; Dogan, Mehmet; Draxl, Claudia; Galli, Giulia; et al. (arXiv:2209.12747)
Electronic structure calculations have been instrumental in providing many important insights into a range of physical and chemical properties of various molecular and solid-state systems. Their importance to various fields, including materials science, chemical sciences, computational chemistry and device physics, is underscored by the large fraction of available public supercomputing resources devoted to these calculations. As we enter the exascale era, exciting new opportunities to increase simulation numbers, sizes, and accuracies present themselves. In order to realize these promises, the community of electronic structure software developers will however first have to tackle a number of challenges pertaining to the efficient use of new architectures that will rely heavily on massive parallelism and hardware accelerators. This roadmap provides a broad overview of the state-of-the-art in electronic structure calculations and of the various new directions being pursued by the community. It covers 14 electronic structure codes, presenting their current status, their development priorities over the next five years, and their plans towards tackling the challenges and leveraging the opportunities presented by the advent of exascale computing.

Towards electronic structure-based ab-initio molecular dynamics simulations with hundreds of millions of atoms - Schade, Robert; Kenter, Tobias; Elgabarty, Hossam; Lass, Michael; Schütt, Ole; Lazzaro, Alfio; Pabst, Hans; Mohr, Stephan; Hutter, Jürg; Kühne, Thomas; Plessl, Christian (Parallel Computing)
Keywords: Artificial Intelligence; Computer Graphics and Computer-Aided Design; Computer Networks and Communications; Hardware and Architecture; Theoretical Computer Science; Software

Effects of verbal negation on TVA’s capacity and weight parameters - Banh, Ngoc Chi; Scharlau, Ingrid (TeaP 2022 - Abstracts of the 64th Conference of Experimental Psychologists)

Folgen wiederholter Negation auf die Aufmerksamkeit - Banh, Ngoc Chi; Scharlau, Ingrid; Rohlfing, Katharina J. (52. Kongress der Deutschen Gesellschaft für Psychologie)